Pengaruh Rasio NPL, LDR, NIM, BOPO, dan CAR Terhadap Profitabilitas Bank BUMN di Indonesia - Yulianah; Seno Aji, Tony (Bisei : Jurnal Bisnis dan Ekonomi Islam, 2021)
Abstract: This study intends to examine the effect of the ratio of NPL, LDR, NIM, BOPO and CAR on Profitability (ROA) in Indonesian State-Owned Banks. The sample taken in this study is a saturated sample, that is, all of the population of these banks are sampled, namely Bank Mandiri, Bank Rakyat Indonesia, Bank Tabungan Negara, and Bank Negara Indonesia with a period of 2016-2020 quarters I to IV. The analysis technique used is panel data regression using Eviews 10 software. The results state that simultaneously NPL, LDR, NIM, BOPO, and CAR have an effect on ROA with an effect of 99.2%. While partially the NPL and NIM variables affect ROA in a positive direction, the BOPO variable affects ROA in a negative direction, the LDR and CAR variables do not affect ROA at state-owned banks in Indonesia. Keywords: NPL, LDR, NIM, BOPO, CAR, ROA